Urban ecological network simulation based on integrated models a case study of Quezon City, Philippines - Alvarez, Aicel Mae J. (College of Architecture, University of the Philippines Diliman, 2019)
Anthropocentric orientation of urban development processes leads to deficiency of areas with significant environmental values in the urban landscapes. As landscape planners try to increase the quality of living in the urban environment, efforts are focused only on the hot spots which often cater only to the recreational needs of urban dwellers. In Quezon City, the LGU plans to create the Green Lung Network featuring a chain of developments linking La Mesa Nature Reserve, the largest green space in Metro Manila, to all the open spaces and parks in the city. However, it does not address the functional and structural connectivity and is focused solely on creating green corridors for human mobility. Moreover, the construction of MRT 7 line will possibly lead to loss of natural habitats and furthers landscape fragmentation. Hence, it is a challenge to connect La Mesa Nature Reserve to other green spaces of the city to create an ecological network which will disperse and enrich biodiversity all over the city. To address this, the study aims to create an ecological connectivity network for Quezon City based on behavior and preference of local species as parameters and indicators for movement along corridors. This study integrated circuit-modelling and least-cost modelling which were parameterized with green space structures such as patch size and vegetation density to optimize corridor effectiveness for the focal species: Passer montanus and Pycnonotus goiaver. This study provided a framework of integrated models, theories, and different GIS tools to identify the focal nodes, create resistance surface, and construct the corridors. In the resulting Network Plan, aside from it does not connect only the ecological cores of Quezon City but also other tiny patches of green spaces, some corridors also crossed the route of MRT 7 line instead of avoiding resulting Ecological Network's corridors and had only seven out of 26 focal nodes. The set of procedures used in this study illustrated how the concept of ecological networks may be integrated into the urban planning process.